2013
DOI: 10.1179/1743284712y.0000000135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain rate on acoustic emission during tensile deformation of α-brass

Abstract: In the present investigation, acoustic emission (AE) technique has been used to study the effect of variation in strain rate on AE signals during tensile deformation of α-brass. Tensile tests have been carried out at four different strain rates, i.e. 3·33×10−4, 6·66×10−4, 1·33×10−3 and 2×10−3 s−1 with simultaneous monitoring of AE parameters. Results indicated that the intensity of AE signals increased with increase in strain rate, which had been attributed to the combined effect of dislocation motion and twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These results are in agreement with the results reported earlier for 316 stainless steel [14,18]. Increase in AE generation with increasing strain rate is also in agreement with the results in ␣-brass [16], where AE is generated by both dislocation motion and twinning. It is also seen from Fig.…”
Section: Acoustic Emissionsupporting
confidence: 95%
See 2 more Smart Citations
“…These results are in agreement with the results reported earlier for 316 stainless steel [14,18]. Increase in AE generation with increasing strain rate is also in agreement with the results in ␣-brass [16], where AE is generated by both dislocation motion and twinning. It is also seen from Fig.…”
Section: Acoustic Emissionsupporting
confidence: 95%
“…Pattnaik et al [16] have shown that AE signal generated during deformation of ␣-brass is strain rate sensitive and intensity of the AE signals increases with strain rate. They have attributed the increase in intensity of AE with increase in strain rate to dislocation motion and twinning.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our recent work on a low stacking fault energy material (brass), we found that the AE signal intensity increased with increase in twinning density. We found a strong correlation of microstructural features (in terms of twinning density) with that of AE signal intensity [13].…”
Section: Introductionmentioning
confidence: 94%
“…The AE cumulative counts were found to increase with increase in Al-5Ti-1B master alloy addition. The AE signals generated in the micro plastic and yielding stage could be attributed to the generation and motion of dislocations from Frank-Read and grain boundary sources [13,25]. The increase in AE activity (counts and amplitude) due to the addition of Al-5Ti-1B master alloy is mainly attributed to the change in morphology of primary-␣ grain from coarse dendritic to fine equiaxed structure.…”
Section: Effect Of Grain Refiner On Mechanical and Acoustic Emission mentioning
confidence: 99%